Cancer and other causes of death among a cohort of dry cleaners. Issue 3 (March 1990) - Blair, A; Stewart, P A; Tolbert, P E; Grauman, D; Moran, F X; Vaught, J; Rayner, J
Abstract : Mortality among 5365 members of a dry cleaning union in St. Louis, Missouri, was less than expected for all causes combined (SMR = 0.9) but slightly raised for cancer (SMR = 1.2). Among the cancers, statistically significant excesses occurred for oesophagus (SMR = 2.1) and cervix (SMR = 1.7) and non-significant excesses for larynx (SMR = 1.6), lung (SMR = 1.3), bladder (SMR = 1.7), thyroid (SMR = 3.3), lymphosarcoma and reticulosarcoma (SMR = 1.7), and Hodgkin's disease (SMR = 2.1). Mortality from emphysema was also significantly raised (SMR = 2.0). Eleven of the 13 deaths from oesophageal cancer occurred among black men. The risk of this cancer showed a significant association with estimated cumulative exposure to dry cleaning solvents (rising to 2.8-fold in the highest category) but not with level or duration of exposure. Mortality from kidney cancer was not excessive as reported in other studies. Excesses for emphysema and cancers of the larynx, lung, oesophagus, bladder, and cervix may be related to socioeconomic status, tobacco, or alcohol use. Although the number of deaths was small, the greatest risk for cancers of the lymphatic and haematopoietic system (fourfold) occurred among workers likely to have held jobs where exposures were the heaviest. Small numbers and limited information on exposure to specific substances complicates interpretation of this association but is unlikely to be due to confounding by tobacco use. It was not possible to identify workers exposed to specific dry cleaning solvents but mortality among those entering the union after 1960, when use of perchloroethylene was predominant, was similar to those entering before 1960.